Visualizing artery‐specific blood flow patterns above the circle of Willis with vessel‐encoded arterial spin labeling. Issue 3 (25th October 2018) - Okell, Thomas W.; Garcia, Meritxell; Chappell, Michael A.; Byrne, James V.; Jezzard, Peter
Abstract : Purpose: To establish the feasibility of using vessel‐encoded pseudocontinuous arterial spin labeling (VEPCASL) for noninvasive vascular territory imaging (VTI) and artery‐specific dynamic angiography of a large number of arterial branches above the circle of Willis within a clinically feasible scan time. Methods: 3D time‐of‐flight angiography was used to select a labeling plane and establish 7 pairs of encoding cycles. These were used for VEPCASL VTI and dynamic 2D angiography (8 min and 3 min acquisition times, respectively) in healthy volunteers, allowing the separation of signals arising from 13 arterial branches (including extracranial arteries) in postprocessing. To demonstrate the clinical potential of this approach, VEPCASL angiography was also applied in 5 patients with brain arteriovenous malformation (AVM). Results: In healthy volunteers, the artery‐specific filling of the vascular tree and resulting perfusion territories were well depicted. SNRs were approximately 5 times higher than those achievable with single‐artery selective methods. Blood supply to the AVMs was well visualized in all cases, showing the main feeding arteries and venous drainage. Conclusions: VEPCASL is a highly efficient method for both VTI and dynamic angiography of a large number of arterial branches, providing a comprehensive picture of vascular flow patterns and the effect on downstream tissue perfusion within an acceptable scan time. Automation of labeling plane and vessel‐encoding selection would improve robustness and efficiency, and further refinement could allow quantitative blood flow measurements to be obtained. This technique shows promise for visualizing the blood supply to lesions and collateral flow patterns.